Dual Roles of an E-Helix Residue, Glu167, in the Transcriptional Activator Function of CooA - Youn, Hwan (American Society for Microbiology, 2005)
CooA is a transcriptional activator that mediates CO-dependent expression of the genes responsible for CO oxidation in Rhodospirillum rubrum. In this study, we suggest in vitro and in vivo models explaining an unusual requirement of CooA for millimolar levels of divalent cations for high-affinity DNA binding. Several lines of evidence indicate that an E-helix residue, Glu167, plays a central role in this requirement by inhibiting sequence-specific DNA binding via charge repulsion in the absence of any divalent cation and that divalent cations relieve such repulsion in the process of DNA binding by CooA. Unexpectedly, the Glu167 residue is the optimal residue for in vivo transcriptional activity of CooA. We present a model in which the Glu167 from the downstream subunit of CooA helps the protein to interact with RNA polymerase, probably through an interaction between activating region 3 and σ subunit. The study was further extended to a homologous protein, cyclic AMP receptor protein (CRP), which revealed similar, but not identical, roles of the residue in this protein as well. The results show a unique mechanism of CooA modulating its DNA binding and transcriptional activation in response to divalent cations among the CRP/FNR (fumarate and nitrate reductase activator protein) superfamily of regulators.